Perlindungan hak asasi manusia dalam hukum acara Mahkamah Konstitusi - Aini, Siti Wardatul (Maliki Interdisciplinary Journal, 2024)
The constitution is the highest law ever made to defend human rights. The fact that Indonesia is a constitutional state committed to recognizing and upholding human rights is evidenced by the existence of articles on human rights in the 1945 Constitution. The 1945 Constitution authorizes the Constitutional Court to conduct a judicial review in order to preserve and guarantee human rights. The judicial review carried out by the Constitutional Court is not only as a guardian of the constitution but also as an institution for safeguarding human rights, as later shown in relation to various decisions of the Constitutional Court.